NADH Oxidase Functions as an Adhesin in Streptococcus pneumoniae and Elicits a Protective Immune Response in Mice - Muchnik, Lena (Public Library of Science, 2013)
The initial event in disease caused by S. pneumoniae is adhesion of the bacterium to respiratory epithelial cells, mediated by surface expressed molecules including cell-wall proteins. NADH oxidase (NOX), which reduces free oxygen to water in the cytoplasm, was identified in a non-lectin enriched pneumococcal cell-wall fraction. Recombinant NOX (rNOX) was screened with sera obtained longitudinally from children and demonstrated age-dependent immunogenicity. NOX ablation in S. pneumoniae significantly reduced bacterial adhesion to A549 epithelial cells in vitro and their virulence in the intranasal or intraperitoneal challenge models in mice, compared to the parental strain. Supplementation of Δnox WU2 with the nox gene restored its virulence. Saturation of A549 target cells with rNOX or neutralization of cell-wall residing NOX using anti-rNOX antiserum decreased adhesion to A549 cells. rNOX-binding phages inhibited bacterial adhesion. Moreover, peptides derived from the human proteins contactin 4, chondroitin 4 sulfotraferase and laminin5, homologous to the insert peptides in the neutralizing phages, inhibited bacterial adhesion to the A549 cells. Furthermore, rNOX immunization of mice elicited a protective immune response to intranasal or intraperitoneal S. pneumoniae challenge, whereas pneumococcal virulence was neutralized by anti-rNOX antiserum prior to intraperitoneal challenge. Our results suggest that in addition to its enzymatic activity, NOX contributes to S. pneumoniae virulence as a putative adhesin and thus peptides derived from its target molecules may be considered for the treatment of pneumococcal infections. Finally, rNOX elicited a protective immune response in both aerobic and anaerobic environments, which renders NOX a candidate for future pneumococcal vaccine.